Seismic analysis of a building block located in an urban area of the Faial Island of Azores - Nuno Neves (2004)
This paper presents part of an ongoing research on the seismic behaviour of a whole building block at Horta (a town in the Faial Island - Azores), hit by an earthquake on July, 9th 1998. The outcome of a preliminary numerical analysis carried out locally on a single building and globally on the whole block is presented, in order to assess sensitivity both to the modelling type and material properties. After a preliminary identification of the most vulnerable areas of this block, an experimental campaign of in situ ambient vibration tests was performed. Through the results, both frequencies and vibration modes of some of the block buildings were obtained, which allowed calibrating the numerical modelling presented herein. Furthermore, numerical seismic analyses were performed for some houses of the block considering the actually recorded accelerograms during that earthquake. The first results obtained to date are briefly addressed and discussed in terms of stress and drift values due to seismic action.